HUBUNGAN KEBIASAAN MAKAN DAN PRAKTIK KEBERSIHAN DIRI DENGAN KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS SIKUMANA KOTA KUPANG - Ni Putu Intan Suseni; Florentianus Tat; Herliana Monika Azi Djogo (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2022)
Introduction: Stunting or short is a condition of failure to thrive in infants (0-11 months) and children under five (12-59) months. The condition of stunting indicates insufficient nutrition for a long time, so it is very important to fulfill adequate nutrition at an early age. Purpose: This study was to determine the relationship between eating habits and personal hygiene practices with the incidence of stunting in children under five in the working area of ​​the Sikumana Community Health Center, Kupang City. Methods: the research design used was analytical correlation with a